Shared decision-making in breast cancer care: Patient preferences and implications for clinical communication - Buizza, Chiara; Bazzana, Debora; Cela, Herald; Mazzi, Maria Angela; Goss, Claudia; Del Piccolo, Lidia; Ghilardi, Alberto (European Journal of Oncology and Environmental Health, 2025)
Introduction: A new cancer diagnosis generates a situation of anxiety, fear and worry for both the present and the future. It is a time of loss, during which patients must choose between different possible ways to manage their disease. It is very important to identify patients’ preferred roles in the decision-making process, together with the factors that can affect patients’ involvement during consultation, so that oncologists can adjust their interpersonal style and communication, providing better patient-centered care. Methods: This study is part of a multi-center RCT and involved 308 early-stage breast cancer patients. We evaluated the preferred role and the variables associated with the patients’ preferred level of involvement during their first consultation with an oncologist. Results: More than half of the subjects preferred a collaborative role and it was the most frequent choice among single and employed women. Patients who preferred a collaborative role asked more questions and had a longer consultation than those who preferred to take a more passive role. Conclusion: These results give rise to new research questions on the role that early-stage breast cancer patients would like to play in the decision-making process concerning their treatment, and on the variables that contribute to their attitudes towards such involvement. The findings suggest that oncologists need to interact with and listen to their patients in an active and empathetic manner, in order to acquire a full understanding of their needs.